Severity of Neuropsychiatric Symptoms in Nursing Home Residents - Anne-Sofie Helvik; Knut Engedal; Bei Wu; Jūratė Šaltytė Benth; Kirsten Corazzini; Irene Røen; Geir Selbæk (Dementia and Geriatric Cognitive Disorders Extra, 2016)
We aimed at assessing time shift in the severity of neuropsychiatric symptoms (NPS) in nursing home residents between 2004/2005 and 2010/2011 and associations between NPS and socio-demographic variables, physical health status, dementia severity, and the use of psychotropic drugs. The Neuropsychiatric Inventory Nursing Home Version was used in 2004/2005 (n = 1,163) and 2010/2011 (n = 1,858). Linear mixed model analysis was applied. There was no time shift in the severity of apathy, psychosis, and affective symptoms, but agitation did exhibit a time shift. Agitation was less severe in 2010/2011 than in 2004/2005 in residents with a Clinical Dementia Rating (CDR) sum of boxes score ≤4, and more severe in residents with a CDR sum of boxes score >16. Higher CDR sum of boxes scores and use of psychotropic medication were associated with more severe apathy, agitation, psychosis, and affective symptoms. Poor physical health was associated with more severe apathy, psychosis, and affective symptoms. Women had more severe agitation and less severe affective symptoms than men. A longer stay in a nursing home was associated with more severe agitation and less severe affective symptoms. In conclusion, agitation was less severe in 2010/2011 than in 2004/2005 among nursing home residents with a milder degree of dementia, and more severe in residents with severe dementia.